Objective Assessment of Rupture Parameters in Intact and Acute Post-Cystorrhaphy Cadaveric Bladders - Geoffrey D. Towers; Dani G. Zoorob; Rose A. Maxwell; Ashley N. Reid; Jerome L. Yaklic; Jason C. Massengill (Clinical and Experimental Obstetrics & Gynecology)
Background: Certain procedures, particularly those used to treat symptoms of bladder pain syndrome/interstitial cystitis (BPS/IC), involve filling the bladder to or over its capacity for visualization and/or relief of symptoms. Rarely, if excessive pressure or volume is used, bladders may rupture causing significant harm to the patient. The purpose of this study was to identify baseline data for pressure and volume when hydrodistention is attempted in explanted cadaveric bladders, as well as determine bladder rupture pressure changes in the acute post-cystorrhaphy state. Methods: Eight explanted cadaveric bladders were filled using a systematic digital pump system. Intravesical pressure and volume were monitored during the filling phase until rupture. A two-layer cystorrhaphy was performed followed by bladder refilling to point of rupture. The pressure-volume correlations were developed for the explanted bladders, pre and post rupture. Results: The mean intact bladder rupture volume was 1186.3 mL ± 356.1 (range 450.0–1550.0) and mean pressure of 103.4 cm H2O ± 45.9 (range 59.0–190.0). The mean bladder rupture volume following repair was 1051.9 mL ± 251.3 (range 500.0–1300.0) while the mean pressure dropped to 53.1 cm H2O ± 44.0 (range 18.0–149.0). Compliance was noted to decrease significantly with a 54% drop in maximal pressure immediately prior to repeat rupture. Location of the initial rupture site did not have an impact on volume or pressures achieved. The weakest point post-cystorrhaphy consistently involved the original cystotomy site. Conclusions: This study provides ex-vivo bladder parameters that may guide providers in distention and post-rupture cases. Repeat rupture pressure (maximal bladder pressure achieved) and bladder compliance were noted to be significantly lower immediately post-cystorrhaphy.